A Case of Calcified Metastatic Colorectal Adenocarcinoma Mimicking a Benign Lesion: Pitfalls in Diagnosis - Peter Michail; Iftah Amith; Sanila George; Mathew K. George (Case Reports in Oncological Medicine)
The radiological finding of a calcified intracranial lesion commonly represents a slow growing benign mass. Brain metastases originating from colorectal cancers are rare, occurring in approximately 2-3% of patients. Therefore the presence of a calcified brain lesion in a patient with a positive oncological history requires a high index of suspicion for brain metastases. Presented herein is a case of a frontoparietal calcified lesion initially overlooked as a benign tumour. Subsequent imaging following a neurological episode revealed a significant increase in size of the lesion with surrounding tissue oedema, prompting further investigation for suspicion of a calcified metastatic colorectal adenocarcinoma.